2021
DOI: 10.4149/gpb_2021018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leukaemia effects of leonurine in vitro and in vivo

Abstract: The present study was conducted to explore the anti-acute myeloid leukaemia (AML) effects of leonurine. HL-60 and U-937 cells were used to assess the antileukaemia effect of leonurine in vitro, and HL-60 and U-937 xenograft nude mice were used to evaluate its antitumour effect in vivo. Leonurine inhibited the proliferation of HL-60 and U-937 cells in a time-and dose-dependent manner. Moreover, leonurine therapy prevented the growth of tumours in both xenograft animal models. Leonurine could induce apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Yuan et al reported that leonurine hydrochloride inhibited the NF-κB and PI3K/Akt signaling pathways, preventing estrogen-efficiencyassociated osteoporosis [18]. Moreover, leonurine inhibits the activation of PI3K/Akt pathway by reducing the phosphorylation levels of PI3K and Akt [8]. To study the signaling mechanisms affected by leonurine in regulation of human breast cancer cells, the effect of leonurine on PI3K/AKT/mTOR pathway was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al reported that leonurine hydrochloride inhibited the NF-κB and PI3K/Akt signaling pathways, preventing estrogen-efficiencyassociated osteoporosis [18]. Moreover, leonurine inhibits the activation of PI3K/Akt pathway by reducing the phosphorylation levels of PI3K and Akt [8]. To study the signaling mechanisms affected by leonurine in regulation of human breast cancer cells, the effect of leonurine on PI3K/AKT/mTOR pathway was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leonurine suppresses colony formation and proliferation and enhances apoptosis of chronic myeloid leukemia cells [7]. Leonurine also inhibits the activity of PI3K/Akt pathway by reducing PI3K and Akt phosphorylation [8]. However, the effects of leonurine on breast cancer and its related mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, we established an in vivo model using the U-937 cell line. We used this cell line because it is more aggressive, has a histiocytic subtype, and exhibits diffuse proliferation; moreover, it is routinely used for the evaluation of antitumor and cytotoxic activity in natural products [ 25 , 26 , 27 , 28 ]. At day 29, we found substantial differences in the weight gains of the left and right inguinal and axillary lymph nodes, compared to our healthy control ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leo displays antitumor effects both in vivo and in vitro, with physiological effects as shown in Figure 1. It exerts its antitumor actions by inducing tumor cell apoptosis and inhibiting tumor cell proliferation, invasion, and migration Hu et al, 2019;Zhuang et al, 2021).…”
Section: Main Antitumor Mechanisms Of Leomentioning
confidence: 99%